Multifunctional materials based on the double-perovskite organic–inorganic hybrid (CH3NH3)2[KCr(CN)6] showing switchable dielectric, magnetic, and semiconducting behaviour. Issue 44 (30th October 2019) - Rok, M.; Moskwa, M.; Działowa, M.; Bieńko, A.; Rajnák, C.; Boča, R.; Bator, G.
Abstract : Herein, we have synthesised and characterised a novel organic–inorganic hybrid crystal, [CH3 NH3 ]2 KCr(CN)6 (MACr ). Abstract : Herein, we have synthesised and characterised a novel organic–inorganic hybrid crystal, [CH3 NH3 ]2 KCr(CN)6 (MACr ). Thermal analysis (DSC, TGA-DTA) indicates one structural phase transition (PT ) at 450 K. The modified equation of the tolerance factor, t, was used to estimate the theoretical PT temperature for a crystal with Mn(iii ). According to the X-ray diffraction experiment, in the low-temperature (LT) phase, the solid-to-solid PT is described by the monoclinic space group C 2/ c . The creation of the ferroelastic domain structure in phase II was proved on the basis of the observation under a polarising microscope. The crystals of MACr and its isomorphous analogues with Fe(iii ) and Co(iii ) appeared to be semiconducting materials in the LT phase. The type of PT is order–disorder and occurs between "low" (ordered-frozen) and "high" (orientationally disordered) dielectric states. Dielectric spectroscopy was used to characterise the switching properties of the dipole moments in the vicinity of the PT s. The magnetic properties of the MACr hybrid were investigated in DC and AC modes. The DC data show a sizeable weak exchange interaction between the nearest Cr(iii ) centres in the crystal lattice. The AC susceptibility data confirm a slow magnetic relaxation in the applied DC field with two relaxation channels. The low-frequency relaxation time is very long as τ LF = 1.4(1) s at T = 2.0 K. The organic–inorganic hybrid, described above, can be considered a rare example of multifunctional materials which exhibit dielectric, magnetic, and conductive activities.